Pharmacological Potentials and Nutritional Values of Tropical and Subtropical Fruits of India: Emphasis on their Anticancer Bioactive Components - Narayanankutty, Arunaksharan (Recent Patents on Anti-Cancer Drug Discovery, 2022)
Background: Fruits are an important dietary component, which supply vitamins, minerals, as well as dietary fiber. In addition, they are rich sources of various biological and pharmacologically active compounds. Among these, temperate fruits are well studied for their pharmacological potentials, whereas tropical/subtropical fruits are less explored for their health impacts. In India, most of the consumed fruits are either tropical or subtropical. Objectives: This mini review aims to provide a health impact of major tropical and sub-tropical fruits of India, emphasizing their anticancer efficacy. In addition, the identified bioactive components from these fruits exhibiting anticancer efficacy are also discussed along with the patent literature published. Methods: The literature was collected from various repositories, including NCBI, ScienceDirect, Eurekaselect, and Web of Science; literature from predatory journals was omitted during the process. Patent literature was collected from google patents and similar patent databases. Results: Tropical fruits are rich sources of various nutrients and bioactive components including polyphenols, flavonoids, anthocyanin, etc. By virtue of these biomolecules, tropical fruits have been shown to interfere with various steps in carcinogenesis, metastasis, and drug resistance. Their mode of action is either by activation of apoptosis, regulation of cell cycle, inhibition of cell survival and proliferation pathways, increased lipid trafficking or inhibiting inflammatory pathways. Several molecules and combinations have been patented for their anticancer and chemoprotective properties. Conclusion: Overall, the present concludes that Indian tropical/ subtropical fruits are nutritionally and pharmacologically active and may serve as a source of novel anticancer agents in the future.
Keywords: degenerative diseases